Electrically conductive and 3D-printable copolymer/MWCNT nanocomposites for strain sensing. (8th February 2023) - Hia, Iee Lee; Snyder, Alexander D.; Turicek, Jack S.; Blanc, Fernanda; Patrick, Jason F.; Therriault, Daniel
Abstract: Structural health monitoring (SHM) of safety-critical composite components is essential to ensure mechanical stasis and detect local damage before it can produce global failure. SHM technologies must also adapt to ever-evolving materials and geometries, but traditional piezoresistive strain sensors lack the ability for end-user customization and modifications throughout service-life. Additive manufacturing via fused filament fabrication (FFF) provides a practical pathway to overcome such sensor shortcomings. However, the electrical conductivity of conventional polymer feedstock is not sufficient for accurate strain measurements without compromise to melt viscosity and thus printability. Here we report the development of a new 3D-printable and electrically responsive nanocomposite by melt-mixing poly(ethylene-co-methacrylic acid) (EMAA) with multi-walled carbon nanotubes (MWCNT). Bulk electrical conductivity of 43.9 S m −1 is achieved at only 5 wt% loading – higher than comparable materials – where the nano-dispersion heterogeneity of MWCNT in EMAA is linked to the favorable conductivity while retaining molten flowability. FFF is employed to print thin ( 150 μ m ) serpentine strain sensors onto the surface of a glass fiber-reinforced polymer composite, which exhibit strong adhesion and accurate piezoresistive sensing under cyclic flexural loading. Twenty consecutive cycles with converged sensor readings (i.e., < 1% variation in measured resistance) demonstrates reliable performance across a relevant service strain range (0.4 – 0.8 %) for such fiber-composites. This rapid fabrication and transferable sensing strategy, suitable for new and existing structures, thus provides a crosscutting SHM solution. Graphical abstract: Highlights: Achieved high electrical conductivity ( > 40 S m −1 ) at low MWCNT loading (5 wt%). Favorable conductivity reached by controlling nano-dispersion of MWCNTs in copolymer. 3D printing onto a glass-fiber composite provides reliable and repeatable strain sensing. Twenty flexural load-unload cycles are demonstrated with minimal sensor hysteresis.